APPLICATION OF RENEWABLE ENERGY SOURCES IN THE CONDITIONS OF KASHKADARYA REGION (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article highlights the available resources of renewable energy sources (solar and wind energy, biogas technology) in the Kashkadarya region and the possibilities of their use.